2015
DOI: 10.1111/tmi.12512
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to reduce the disparity between permanent residents and temporary migrants: Stop TB experiences in Shanghai, China

Abstract: Abstractobjective Eight of 17 districts of Shanghai have offered transportation and living allowances subsidies to patients with tuberculosis (TB) among the migrant population. The study aimed to assess the impact of the subsidising initiative on the treatment success rate (TSR) and identify the social determinants of treatment outcomes. conclusions Besides free medical services, transport and living allowance subsidies to migrant patients with TB improved the treatment outcome significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
2
15
1
1
Order By: Relevance
“…Socially marginalized, high-risk subgroups commonly experience access barriers to TB care that result in poor treatment outcomes [14]. Economic migrants, defined as non-permanent residents in search of economic opportunity [15,16], constitute a key affected population. These migrants may face systemic barriers to housing, education, financing and healthcare (Table 1) [17,18].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Socially marginalized, high-risk subgroups commonly experience access barriers to TB care that result in poor treatment outcomes [14]. Economic migrants, defined as non-permanent residents in search of economic opportunity [15,16], constitute a key affected population. These migrants may face systemic barriers to housing, education, financing and healthcare (Table 1) [17,18].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…3,4 Heng County is a key area in the Guangxi Beibu Gulf Economic Zone, with a large transient population that promotes the spread of tuberculosis. 5,6 Currently, the prevalence of human immunodeficiency virus (HIV)-tuberculosis coinfections represent a serious new challenge to the public health system. In 2011, about 1.1 million (13%) of the 8.7 million people infected with tuberculosis worldwide were HIVpositive.…”
Section: Introductionmentioning
confidence: 99%
“…44 As prior evidence has shown, the use of incentives and subsidies, and support for side effect management can also have a significant positive impact on TB treatment outcomes in urban migrants. 16,45 Even though our comparative ITS analysis on the subpopulation of temporary residents failed to detect a significant change after implementation of the intervention possibly due to data sparsity, it may be reasonable to extend our findings to economic migrants given their high proportion in the general population (~38%) and TB patient cohort (23%) of Go Vap. The disparity in these two proportions also reinforces the WHO recommendation of systematic screening among migrants, as studies have shown that intensified case finding along with patient education, advocacy and robust referral mechanisms can have a positive impact on detection within this vulnerable group.…”
Section: Discussionmentioning
confidence: 74%